Perancangan Toilet DU – 3E Bagi Masyarakat Indonesia - Melindawati Muchtar; Anda Iviana Juniani; Wiediartini Wiediartini (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Water is an important element for the life of living things on earth. However, the high levelof human need for clean water is not comparable to the level of availability. The decrease of cleanwater sources in Indonesia due to pollution by pentogen bacteria, such as E. coli. These bacteriacome from sanitation systems in Indonesia. This research will design a toilet with the basic principleof DU - 3E. Toilet ergonomics, ecological, easy maintenance, difable availability, and user centeredfor the people of Indonesia. Toilet design development uses the Ulrich method to get the best design.A list of concept needs was obtained through researchers observations of disability needs whenengaged in toilet activities. In addition, an ergonomic approach is carried out through theanthropometric approach of the Indonesian people. The toilet designed by the basic principle of